Validity and reliability of the Malay language Perception Towards Smoking Questionnaire (BM-PTSQ) among secondary school adolescents: Further validation using Confirmatory Factor Analysis - Kuang Hock Lim; Yoon Ling Cheong; Hui Li Lim; Kee Chee Cheong; Mohd Hazilas Mat Hashim; Ali Aman Marine; Yong Kang Cheah; Jia Hui Lim; Sumarni Mohd Ghazali (Tobacco Induced Diseases)
Introduction Perception is an essential factor influencing smoking among adolescents. Thus, a valid tool for measuring perception is a requisite in smoking studies. This study further establishes the validity and reliability of a Malay language version of the Perception Towards Smoking Questionnaire (BMPTSQ) for assessing the perception of smoking among secondary school-going adolescents in Malaysia.